Precision repair of zone-specific meniscal injuries using a tunable extracellular matrix-based hydrogel system - Se-Hwan Lee; Zizhao Li; Ellen Y. Zhang; Dong Hwa Kim; Ziqi Huang; Yuna Heo; Sang Jin Lee; Hyun-Wook Kang; Jason A. Burdick; Robert L. Mauck; Su Chin Heo (Bioactive Materials)
Meniscus injuries present significant therapeutic challenges due to their limited self-healing capacity and the diverse biological and mechanical properties across the tissue. Conventional repair strategies do not replicate the complex zonal characteristics within the meniscus, resulting in suboptimal outcomes. In this study, we introduce an innovative fetal/adult and stiffness-tunable meniscus decellularized extracellular matrix (DEM)-based hydrogel system designed for precision repair of heterogeneous, zonal-dependent meniscus injuries. By synthesizing fetal and adult DEM hydrogels, we identified distinct cellular responses, including that hydrogels with adult meniscus-derived DEM promote more fibrochondrogenic phenotypes. The incorporation of methacrylated hyaluronic acid (MeHA) further refined the mechanical properties and injectability of the DEM-based hydrogels. The combination of fetal and adult DEM with MeHA allowed for precise tuning of stiffness, influencing cell differentiation and closely mimicking native tissue environments. In vivo tests confirmed the biocompatibility of hydrogels and their integration with native meniscus tissues. Furthermore, advanced 3D bioprinting techniques enabled the fabrication of hybrid hydrogels with biomaterial and mechanical gradients, effectively emulating the zonal properties of meniscus tissue and enhancing cell integration. This study represents a significant advance in meniscus tissue engineering, providing a promising platform for customized regenerative therapies across a range of heterogeneous fibrous connective tissues.